Evaluation and Assessment of Growth, yield and uptake of Various non local Barley Cultivars Irrigated with Simulated Wastewater - Zakiyeh Suliman Salem Namrotee (My University, 2016)
The experiment was implemented in order to study the effect of irrigation with simulated wastewater on soil, growth and yield 7 introduced barley cultivars; and to evaluate the impact of using simulated wastewater in irrigation on the plants , and finally the modeling. The experiment was conducted at the new campus of An-Najah National University. The seeds were planted in the spring season 2014, in separated plastic containers filled with 45 kg sandy clay soil, 15 plants were planted in each container, the distribution of the plots was completely randomized plot design. The plants were irrigated with two types of water as experiment treatment (Fresh water as control and simulated wastewater), with three replicates for each treatment. Chemical analysis has been used for determining the mineral contents of the soil of the experiment for each variety and each type of water for Nitrogen (N), Phosphorous (P) , Potassium (K) and total dissolved solids (TDS). These tests were performed at An-Najah National University Laboratories. Each test was done in accordance to standard methods of analyses for soil and water. All collected data were analyzed statistically using one way analysis of variance to examine treatment effects, means were separated by Duncan's multiple range test at P≤ 0.05. Results show that water type has no effect on the growth vigor and nature of all barley cultivars, whereas tiller number was highly affected by water type where cultivars irrigated with simulated wastewater showed significantly higher number of tellers per plant than those irrigated with fresh water. Plants irrigated with both simulated wastewater and freshwater required nearly the same time to emergence, stem elongation, flowering and maturity while significant differences were observed between the barley cultivars. The highest yield was obtained from cultivars irrigated with simulated wastewater, the cultivars irrigated with simulated wastewater gave nearly twice the yield and spike weight than the cultivars irrigated with freshwater. Also plants irrigated with simulated wastewater gave higher spikes length and higher stem weight. On the other hand, Soil irrigated with simulated wastewater absorbed more nitrogen than the soil irrigated with freshwater, the nitrogen absorbed mainly in the root which had the higher N % compared with amount absorbed by both the stem and the spike, where the N% of the spike was nearly higher than the stem (N% – Root > N%- Spike , N% - Stem). For potassium, Plant absorbed it through the root , spike and stem and that’s related to the fact that the potassium is slowly move in the soil in addition to that it react with the elements found in the simulated wastewater and thus decreased in the plants (K% – Stem> K%- Root , K% - Spike). The soil irrigated with simulated wastewater absorbed more phosphorous than the soil irrigated with freshwater, the phosphorous absorbed mainly in the spike which had the higher P% compared with amount taken by both the stem and the root, where the P% of the root was nearly higher than the stem (P% – Spike > P%- Stem , P% - Root). The Model equation according to the results obtained will be: Y = - 4.441 + 0.448* X1 + 18.709 * X2 The obtained model could be helpful when used to calculate the yield to the plants when the amount of water used for irrigation and the weight of the seeds before the planting were known. It should be concluded that barley proved to be a salt-tolerant crop with considerable economic importance. Barley could tolerate saline water without any shortage in the yield of the crop; also, the growth vigor as well as the growth period (from days to emergence to maturity) were not affected with the type of water and only depend on the type of the seeds. In addition, Simulated wastewater is a promising water resource as alternatives for fresh water to be used in agriculture specially crops with high tolerance to salinity such as barley since the use of simulated wastewater in irrigation increases the nitrogen (N), phosphorous (P) and potassium (K) contents in soil profiles and the quality of water used in irrigation affects the soil texture through increasing the concentrations of some constituents such as nitrogen potassium and phosphorous.

تم تطبيق هذه التجربة من أجل دراسة تأثير الري طويل الأمد باستخدام المياه العادمه على التربة وعلى نمو وإنتاج سبعة أصناف من بذور الشعير من أجل تقييم تأثير إستخدام المياه العادمه في الري على الصحة العامة وكذلك دراسة ونمذجة تقييم الأثر البيئي .تم إجراء هذه التجربة في الحرم الجامعي الجديد في جامعه النجاح الوطنيه حيث تمت عمليه زراعه البذور خلال فصل الربيع من العام2014 في أحواض بلاستيكية منفصله تحتوي على تربه رمليه طينيه "45 كغم " بمعدل 15 بذرة في كل حوض . وقد تم توزيع الأحواض بشكل عشوائي ثم تم ري النباتات بنوعين من المياه خلال التجربه " المياه العذبة كمرجع والمياه العادمه " بمعدل ثلاث متكررات لكل صنف. أستخدِمت التحليلات الكيميائيه من اجل حساب محتوى التربه من النيتروجين والفسفور والبوتاسيوم وكذلك الملوحة لكل صنف من الاصناف المرويه بالمياه العذبه والعادمه . هذا وقد تم اجراء هذه التجارب في مختبرات جامعه النجاح الوطنيه حسب قواعد التحليل الاساسيه المستخدمه لحساب التربه والماء. تم استخدام التحليل الاحصائي لجميع البيانات التي تم جمعها لدراسة تأثير المياه باستخدام تحليل الانحدار الخطي بحدود ثقه(P≤0.05). أظهرت النتائج بأنه لا يوجد تأثير لنوعيه المياه على قوة وطبيعة نمو أصناف الشعير, بينما تأثرت عدد السبلات بنوعيه المياه حيث أظهرت النتائج بأن عدد السبلات للنبته الواحده كان أكبر في حالة استخدام المياه العادمه بالري .كما أن النباتات المرويه بالمياه العادمه والعذبه على حد سواء استغرقت نفس الوقت تقريبا للانبات, ظهور الساق, الازهار وكذلك النضوج مع وجود فروقات بسيطه بين اصناف الشعير المستخدمه. الانتاج كان أكبر في حالة النباتات المرويه بالمياه العادمه, حيث اظهرت النتائج ان النباتات التي تم ريها بالمياه العادمه اعطت تقريبا ضعف الانتاج ووزن السنبله من تلك التي تم ريها بالمياه العذبه . كما اظهرت النباتات المرويه بالمياه العادمه وزنا أكبر للجذور وقياسا أطول لطول السنابل. من ناحية اخرى فان النباتات المرويه بالمياه العادمه أظهرت قدرة أكبر على امتصاص الملوحه من تلك المرويه بالمياه العذبه, كذلك أظهرت النباتات التي تم ريها بالمياه العادمه قدرة اكبر على امتصاص النيتروجين من التربه من تلك المرويه بالمياه العذبه حيث تركزت الكميه الاكبر من النيتروجين في الجذور يليها السنبلة واخيرا في الساق . بالنسبه للبوتاسيوم فهو يتركز بشكل كبير في الساق ثم في الجذر واخيرا في السنبلة وذلك يعود لكونه عنصر بطئ الحركة داخل التربه كما انه يتفاعل مع المكونات الموجوده في المواد العادمه . واخيرا أظهرت النتائج أيضا أن عنصر الفسفور يتركز بشكل كبير في السنبله يليها الساق واخيرا في الجذر وهذا لوحظ بشكل أكبر في النباتات المرويه بالمياه العادمه . بناء على النتائج التي تم الحصول عليها من التجربه تم الحصول على المعادله التاليه : Y = - 4.441 + )0.448* X1( + )18.709 * X2( وتهدف هذه المعادله لحساب كميه الانتاج من النباتات عندما تكون كميه المياه المستخدمه في الري وكذلك وزن البذور معروفا قبل عمليه الزراعه . مما سبق يمكن اعتبار نبات الشعير من النباتات المقاومه للملوحه حيث أظهرت الدراسه أنه يستطيع إحتمال الملوحه دون أن تتأثر انتاجيه النبات أو قوة وشدة النمو. وكذلك فترة النمو من بداية الإنبات وحتى النضوج لم تتأثر بنوعيه المياه واعتمدت فقط على نوعيه الاصناف وبالتالي يمكن اعتبار المياه العادمه كمصادر واعدة بديله للمياه العذبة المستخدمة في الزراعه خاصة في المحاصيل المتحملة للملوحة مثل نبات الشعير. كما انها تسهم في زياده نسبه العناصر الاساسيه مثل النيتروجين والفسفور والبوتاسيوم في التربه مما يسهم في تحسين نوعيه وانتاج النبات .
تقييم وتقدير نمو وإنتاج وإمتصاص أصناف شعير غير محلية مروية بمياه عادمة